Some bacteraemias encountered in hospital practice - Crowley, Nuala (1970)
This is a retrospective study of the results of 4,642 blood cultures taken from 2,190 patients from 1960 to 1967 in one London hospital. The results suggested that an increased incidence of bacteraemias at this particular hospital was mainly due to the increase in the number of patients having blood cultures. Some of the bacteraemias were terminal or transient and probably of doubtful clinical significance.